Perfect absorption in 1D photonic crystal nanobeam embedded with graphene/Al2O3 multilayer stack. (May 2018) - Liu, Hanqing; Zha, Song; Liu, Peiguo; Zhou, Xiaotian; Bian, Li-an
Abstract: We exploit the concept of critical coupling to graphene based chip-integrated applications and numerically demonstrate that a perfect absorption (PA) absorber in the near-infrared can be obtained by graphene/Al2 O3 multilayer stack (GAMS) critical coupling with a resonant cavity in the 1D photonic crystal nanobeam (PCN). The key point is dynamically matching the coupling rate of incident light wave to the cavity with the absorbing rate of GAMS via electrically modulating the chemical potential of graphene. Simulation results show that the radius of GAMS as well as the thickness of Al2 O3 layer are closely connected with the performance of perfect absorption. These results may provide potential applications in the high-density integrated optical devices, photolectric transducers, and laser pulse limiters. Highlights: We propose a novel photonic crystal nanobeam (PCN) based on graphene/Al2 O3 multilayer stack (GAMS). The permittivity of GAMS can be modulated apparently through bias voltage. The light-graphene interaction is enhanced a lot in the defect cavity embedded with GAMS. The perfect absorption can be achieved easily in our proposed PCN by tuning the chemical potential of GAMS.